Social Set Visualizer (SoSeVi): Design, development and evaluation of a visual analytics tool for computational set analysis of big social data - Benjamin Johannes Flesch (Copenhagen Business School (CBS), 2019)
This dissertation presents the design, development and evaluation of the Social Set Visualizer, an innovative Visual Analytics software tool, that expands upon a novel set-based approach to Big Social Data Analytics for large-scale datasets from social media platforms such as Facebook. Over the course of five peer-reviewed publications, three different versions of the Visual Analytics software tool are iteratively designed and developed, and several contributions to the visualization of sets and set intersections are highlighted. In seven case studies with the Social Set Visualizer software tool the generation of meaningful facts and actionable insights from Big Social Data are empirically demonstrated, and a pre-existing research gap with regard to the Visual Analytics of large-scale Facebook datasets vs. other social media platforms is closed. Based on these studies, the dissertation puts forward a generalized conceptual model for interactions within Big Social Data termed the Social Interaction Model, which provides a simplification and extension of previous theoretical and formal models.
hdl:10398/9740
Keywords: 650; Visualisierung; Big Data; Social Web